USE OF WORD CARDS MEDIA TO IMPROVE STUDENTS’READING COMPRESHENSION IN LEARNING INDONESIA LANGUAGE FOR CLASS 1 - Virgilius Bate Lina; Theresia Titi Koten (Media Inovasi Pendidikan dan Publikasi, 2024)
Education in elementary school is a very important thing to achieve. One aspect of language skills that is possessed and developed is reading skills. Reading also uses thought, psycholonguistic and metacognitive. Activities to obtain meaning from reading require mastering the language used by the author, so readers need to activate their mental processes and cognition. This type of research is classroom action research (PTK). Classroom action research is carried out in cycles consisting of planning, action, observation and reflection. The results of classroom action research carried out in cycle I, in cycle I there were 13 students who completed the learning activities. The KKM for this load is 70. Meanwhile, in cycle 2, differences begin to occur. Based on the results of research conducted in class 1, researchers can conclude that learning outcomes in Indonesian language subjects regarding syllables have improved with the help of word card media. This can be seen from the learning results of class 1 students, there was an increase after implementing learning through word card media.